Le vertige de la différenciation, tropisme de la pensée stratégique dans le champ du marketing et de la communication ? - Erik Bertin (Communication)
The search for differentiation is central to the strategies and practices in the field of marketing and mass communication. Rivalry is structurally embedded, thus forcing imitation and differentiation into a binding circulatory relationship. By correlating the two dimensions of intensity and extension, one can calibrate the positioning of competing products, thus revealing the range of the logics behind the strategies of imitation and differentiation.